Systematic Systemic Stress Tests - Thomas Breuer; Martin Summer (Oesterreichische Nationalbank (OeNB), 2018)
For a given set of banks, which economic and financial scenarios will lead to big losses? How big can losses in such scenarios possibly get? These are the two central questions of macro stress tests. We believe that most current macro stress testing models have deficits in answering these questions. They select stress scenarios in a way which might leave aside many dangerous scenarios and thus create an illusion of safety; and which might consider highly implausible scenarios and thus trigger a false alarm. With respect to loss evaluation most stress tests do not include tools to analyse systemic risk arising from the interactions of banks with each other and with the markets. We make a conceptual proposal how these shortcomings may be addressed and how stress tests could be made both systematic and systemic. We demonstrate the application of our concepts using publicly available data on European banks and capital markets, in particular the EBA 2016 stress test results.
Keywords: C18; C44; C60; G01; G32; M48; 330; Stress Testing; Risk Measures; Scenario Analysis; Systemic Risk